2019
DOI: 10.1186/s13046-019-1278-9
|View full text |Cite
|
Sign up to set email alerts
|

UBL4A inhibits autophagy-mediated proliferation and metastasis of pancreatic ductal adenocarcinoma via targeting LAMP1

Abstract: Background Ubiquitin-like protein 4A (UBL4A) plays a significant role in protein metabolism and the maintenance of cellular homeostasis. In cancer, UBL4A represses tumorigenesis and is involved in various signaling pathways. Pancreatic ductal adenocarcinoma (PDAC) is still a major cause of cancer-related death and the underlying molecular mechanism of UBL4A and PDAC remains unknown. Methods First, the prognostic role of UBL4A and its expression in human PDAC patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 51 publications
(59 reference statements)
1
44
1
1
Order By: Relevance
“…Other evidence also suggests that metabolic changes in PDAC drive the transcriptional activation of lysosome biogenesis [46]. A recent study has identified ubiquitin-like protein 4A (UBL4A), a tumor suppressor mediating cell death in response to DNA damage [47], and a protein folding chaperone [48], to directly interact with LAMP1 [49]. The interaction between UBL4A and LAMP1 is thought to disturb lysosome function and thus impair autophagic degradation, as observed by the autolysosome accumulation and lysosomal disfunction in cells with higher UBL4A levels [49].…”
Section: Ubl4amentioning
confidence: 99%
See 1 more Smart Citation
“…Other evidence also suggests that metabolic changes in PDAC drive the transcriptional activation of lysosome biogenesis [46]. A recent study has identified ubiquitin-like protein 4A (UBL4A), a tumor suppressor mediating cell death in response to DNA damage [47], and a protein folding chaperone [48], to directly interact with LAMP1 [49]. The interaction between UBL4A and LAMP1 is thought to disturb lysosome function and thus impair autophagic degradation, as observed by the autolysosome accumulation and lysosomal disfunction in cells with higher UBL4A levels [49].…”
Section: Ubl4amentioning
confidence: 99%
“…A recent study has identified ubiquitin-like protein 4A (UBL4A), a tumor suppressor mediating cell death in response to DNA damage [47], and a protein folding chaperone [48], to directly interact with LAMP1 [49]. The interaction between UBL4A and LAMP1 is thought to disturb lysosome function and thus impair autophagic degradation, as observed by the autolysosome accumulation and lysosomal disfunction in cells with higher UBL4A levels [49]. Furthermore, the analysis of UBL4A expression in 69 PDAC patients revealed that patients with higher levels of UBL4A mRNA in PDAC tissue have improved survival rates [49], perhaps due to also having lower autophagy levels.…”
Section: Ubl4amentioning
confidence: 99%
“…The other DUBs identified in our screen had a much lower Spearman correlation than that of USP1 and TAZ (UCK2: rho = 0.18; UBL4A: rho = −0.13; UCHL1: rho = 0.29). Since USP1 is known to act in an oncogenic manner while UCHL1 and UBL4A are shown to have tumor-suppressive functions, we focused our studies on how USP1 alters TAZ [ 27 , 28 , 29 ]. To understand the expression of USP1 and TAZ at the protein level, we analyzed a panel of breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…PDAC is a common malignant tumor worldwide. [31][32][33][34] Although different approaches are offered for the treatment of PDAC, all deliver unsatisfactory results, characterized by high levels of tumor metastasis and poor prognosis. Thus, there is an urgent need to develop novel therapeutic strategies that have high efficacy with low adverse effects for targeting malignant tumors, especially metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%